Warren Buffett Speaks: Wit and Wisdom from the World's Greatest Investor - Lowe Janet (U.S.A : Wiley, 2007)
Investors around the globe worship Warren Buffett, the "Oracle of Omaha," and British businessman O'Loughlin is no different. Buffett, after all, jostles with Bill Gates for the title of richest man in America and has built Berkshire Hathaway from a small textile concern into a multi-billion-dollar corporate mammoth. So how does he do it? O'Loughlin tackles the question enthusiastically, laying out Buffett's investing strategies, his management techniques and his unconventional wisdom. Much of it is already well known, of course, from Buffett's love of the cash-generating insurance business, to his hands-off managerial style, to his early passion for the ideas of value-investing guru Benjamin Graham. But the book is a useful distillation of everything business buffs know about the inscrutable Buffett. After the dot-com years, during which his plodding investing style went out of favor, it was he who emerged from the bust relatively unscathed. As O'Loughlin fawns, "We may never see the like of Warren E. Buffett again."
Contents
Part I: People Leader 25
2 Berkshire Hathaway and the Institutional Imperative 27
3 Leadership and the Allocation of Capital 51
4 Making Acquisitions Work 81
5 Insurance: Warren Buffett’s Bank 109
Part II: Capital Manager 129
6 The Man for All Seasons 131
7 The Circle of Competence 149
Part III: To Act Like an Owner 175
8 The User’s Manual 177
9 The Circle of Illusory Competence 202
10 Future Knowable
Keywords: Warren Buffett; Kinh tế -- Nhà quản lý; Kinh tế -- quản lý